Os efeitos da comunicação na gestão de equipes multilocalizadas de projetos - Nascimento, Marianna Esteves (2023)
This study is developed in order to illustrate the influence of communication and how it affects multi-located teams in project environments. Due to increasing improvements and changes, companies seek, in addition to efficiency in projects, a trend that teams are not crowded in the same environment. These companies are adapting to new work configurations, aiming at both facilitations and time and cost savings. Multilocalized teams are the bet of the new project environments; however, among the challenges encountered with distance are the difficulty of communication, the need for renewal in the way of leading, more profound leadership skills that can be met at a distance, cultural and linguistic difficulties, as well as the management and the way to share knowledge more effectively through communication improvements. This new format demands more complexity from teams compared to teams in the same environment that have physical contact. Our goal is to understand the influence of communication in multi-location project teams, and how communication affects the ways of managing and sharing knowledge in multi-location project teams. To achieve this goal, two methodological procedures were adopted. At first, we opted for the realization of a systematic literature review (SLR). After searching the databases, 184 articles were found, through a qualitative research. Based on a study of observation of previous studies, without experiments, only the changes over time in the scenarios of projects and multisite environments during the second half of 2021 and first half of 2022, to better understand how this change influenced the behaviors within organizations. For the second step, a case study methodological proposal developed through interviews and analysis of the transcripts through comparative graphs. The study has the differential to illustrate how through communication the management and sharing of knowledge, besides the environment as a whole becomes more effective and how for the organizations multi-localized teams are important, besides covering all these points in a single study, adding to the organizations and to the literature.